Marital Conflict, Allostatic Load, and the Development of Children's Fluid Cognitive Performance - Hinnant, J. Benjamin (2013)
Relations between marital conflict, children’s respiratory sinus arrhythmia (RSA), and fluid cognitive performance were examined over three years to assess allostatic processes. Participants were 251 children reporting on marital conflict, baseline RSA and RSA reactivity to a lab challenge were recorded, and fluid cognitive performance was measured using the Woodcock-Johnson III. A cross-lagged model showed that higher levels of marital conflict at age 8 predicted weaker RSA-R at age 9 for children with lower baseline RSA. A growth model showed that lower baseline RSA in conjunction with weaker RSA-R predicted the slowest development of fluid cognitive performance. Findings suggest that stress may affect development of physiological systems regulating attention, which are tied to the development of fluid cognitive performance.